Prejudices Against Certain Minority Groups and Attitudes Towards Punishment - Bučar Ručman, Ale; Erčulj, Vanja (10. Nacionalna konferenca o varnosti v lokalnih skupnostih: Mirna, varna in inkluzivna družba ter varnost v lokalnih skupnostih, 2024)
Minority groups are often targets of negative prejudices and stereotypes, forming the basis of “us” vs. “them” divisions. This creates a generalized negative image of the Other, affecting all group members. This paper discusses two groups commonly stereotyped in Slovenia and Europe: the Roma and refugees/asylum seekers. Public opinion surveys show high intolerance and social distance towards these groups, influencing citizens’ attitudes and behaviours. The research aimed to examine prejudices against these minority groups in Slovenia and the attitudes of students at the Faculty of Criminal Justice and Security, University of Maribor, towards their punishment. The findings indicate differences in students’ attitudes towards punishment and reoffending based on whether the perpetrator belongs to a minority or majority group. These divisions are also evident in the general public’s attitudes.